PENINGKATAN HASIL BELAJAR IPA MATERI SISTEM PEREDARAN DARAH MANUSIA PADA SISWA KELAS VA SDN BENCONGAN VI - Pandu, Farahiyah Badzlina; Syofyan, Harlinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of good learning can be seen from the determination of the learning method that chosen by teacher. Learning method that suitable will makes active students and get maximum learning outcomes as well as meaningful learning. In elementary school, science cannot only be in the form of theory and memorize, but also provides direct experience to increase students’ competencies. Teachers can use the demonstration method and demonstrating a process or event with real or imitation objects to students. Their thinking skills can arise when there are problems that they have to solve. This study aims to determine the improving learning outcomes on science lesson of human circulatory system through application demonstration learning method for fifth grades at SDN Bencongan VI with the classroom action research. The result showed that in the first cycle is 68% and the second cycle increased to 91%. The highest score of teacher avtivity also increased in second cycle to 90% and the highest score of students activity is 87,5% in the very good category.